The day after tomorrow - Gordon, Mark; Emmerich, Roland; Twentieth Century Fox; Centropolis Entertainment; Lions Gate Films ([Beverly Hills, Calif] : Twentieth Century Fox, 2004)
When global warming triggers the onset of a new Ice Age, tornadoes flatten Los Angeles, a tidal wave engulfs New York City and the entire Northern Hemisphere begns to freeze solid. Now, climatologist Jack Hall, his son Sam, and a small band of survivors must ride out the growing superstorm and stay alive in the face of an enemy more powerful and relentless than anything anyone has ever encountered: Mother Nature
Title from title screen
Screenplay by Roland Emmerich & Jeffrey Nachmanoff
Cast: Dennis Quaid, Jake Gyllenhaal, Ian Holm, Emmy Rossum, Sela Ward, Dash Mihok, Kenneth Welsh
DVD format
Dolby Digital
With optional English, Cantonese, Mandarin, Korean, Thai, Tagalog and Bahasa subtitles
Keywords: Global warming -- Drama; Climatologists -- Drama; Glacial epoch -- Drama